حيادية معدلات الفائدة وحتمية استهداف التضخم في الجزائر - زناقي, سيداحمد; سيدي يخلف, انيسة (جامعة الوادي - University of Eloued, 2019)
تهدف هذه الورقة إلى دراسة واقع السياسة النقدية في الجزائر من أجل فهم متطلبات وتحديات السياسة النقدية في الجزائر في ظل حتمية استهداف التضخم، حيث قمنا بتسليط الضوء على الأدبيات المتعلقة بمختلف استراتيجيات السياسة النقدية بالتركيز على سياسة استهداف التضخم كقاعدة استهداف، وقاعدة Taylor كقاعدة أدوات، كما قمنا بتحليل متغيرات وتشريعات السياسة النقدية في الجزائر. وتوصلنا إلى ضرورة وضع بنك الجزائر لاستراتيجية واضحة، تتضمن أهداف محددة واستقلالية أكبر للبنك المركزي من أجل التسيير الأمثل للسياسة النقدية. This paper aims to analyse the Algerian monetary policy in order to understand the requirements of monetary policy in Algeria taking into account the necessity of targeting inflation. We first shed light on the littérature concerning monetary policy strategies, with a special focus on the inflation targeting policy and Taylor rule. We also analysed the Algerian monetary policy variables and legislations. The results of our paper show that the bank of Algeria has to adopt a clear straegy that includes well-defined objectives and more central bank independence in order to have a monetary policy that works well.
Keywords: سياسة نقدية ; قاعدة ; تقدير ; استهداف التضخم ; قاعدة Taylor ; استراتيجية